Electrophysiological Evidence of Local Sleep During Yoga Nidra Practice - Datta, Karuna; Mallick, Hruda Nanda; Tripathi, Manjari; Ahuja, Navdeep; Deepak, K. K. (Frontiers in Neurology, 2022)
Background and Objectives: Yoga nidra is a technique sages use to self-induce sleep. Classically, sleep is characterised by three cardinal electrophysiological features i.e. electroencephalography, electromyography and electrooculography. As literature on electrophysiological characterisation of Yoga nidra is lacking, it is not known whether it is a sleep or awake state. The objective of the study was to electrophysiologically characterise yoga nidra practice. Materials and Methods: Thirty subjects underwent five initial supervised yoga nidra sessions and then continued practice on their own. The subjects completed their sleep diaries for 2 weeks before and during the intervention. Electrophysiological characterisation was done after 2 weeks of yoga nidra practice using 19 EEG channels polysomnography for pre yoga nidra, yoga nidra practice and post yoga nidra. Polysomnographic data was scored for sleep-wake stages as per standard criteria. Power spectral density (PSD) was calculated from various frequency bands in different time bins. EEG data was grouped by areas: central, frontal, prefrontal, parietal, temporal, and occipital in time bins. Sleep diary parameters were also compared for pre-post yoga nidra training. Results: After 2 weeks of yoga nidra practice, awake was scored throughout the session (n = 26). PSD results (mean difference in dB, between different time bins; P value) showed significant changes. Increased delta power during yoga nidra at central area (1•953; P = 0.033) and reduction in prefrontal area (2•713; P = 0.041) were seen when compared to pre yoga nidra. Sleep diary showed improvement in sleep duration (P = 0.0001), efficiency (P = 0.0005), quality (P = 0.0005) and total wake duration (P = 0.00005) after 2 weeks of practice. Interpretations and Conclusions: Yoga nidra practice in novices is electrophysiologically an awake state with signs of slow waves locally, often referred to as local sleep.